Penny Pinchers Healthy Grocery Store Tour Training Slides - Kolasa, Kathryn M; Smith, Brittany; Ashe, Gerri; Thomas, De'Vette; White, Quatavia (My University, 2024)
This slide set was created by Registered Dietitian Nutritionists in partnership with Pitt Partners for Health (PPH) to be used to train volunteers that will lead or assist with the Penny Pincher's Grocery Store Tour program. It provides basic tour information, a tentative outline of activities, and explains helpful tools at the grocery store that can make shopping for healthy and affordable items easier like Guiding Stars, WIC shelf-tags, and unit prices. Each "stop" along the grocery store tour is reviewed along with key messages that should be communicated with tour participants.
Keywords: Grocery Store Tour; Healthy Eating; Shopping on a budget; Guiding Stars